Exploring Anxiety and Self-Efficacy in Writing: a Case of an English Preparatory Program - Göncü, Selen; Mede, Enisa (Journal of English Studies, 2022)
This paper investigates the level and type of writing anxiety among Turkish EFL students along with the causes of the anxiety perceived by them and their instructors. The EFL writing self-efficacy level of the students was examined, and with the findings obtained, the relationship between writing anxiety and writing self-efficacy in EFL classes was investigated. To meet these objectives, 176 (A2, intermediate level) Turkish EFL students and 6 instructors enrolled in a language preparatory program offered by a state university in Istanbul, Turkey participated in the study. The data were gathered both quantitative and qualitatively through the Second Language Writing Anxiety Inventory (SLWAI), Self-efficacy in Writing Scale (SWS), Causes of Writing Anxiety Inventory (CWAI), and semi-structured interviews. The results revealed that the students had either a high or moderate level of writing anxiety in English, and they mostly suffered from cognitive anxiety. Their level of writing self-efficacy was also moderate, and there was a negative correlation between self-efficacy and writing anxiety among the participants. The results of this study suggest implications about coping with anxiety and self-efficacy in writing classes at language preparatory programs.